AMMI and GGE biplot analysis of yield performance of wheat genotypes under irrigated, heat stress and heat drought environments - Timalsina, Bibisha; Ghimire, Sweksha; Roka, Puja; Poudel, Rashmi; Sapkota, Sushma; Bhattarai, Kriti; Aryal, Anil; Ganesh , G. C.; Neupane, Kapil; Gautam, Pratik; Pariyar, Manoj Kumar; Sharma, Surakshya; Chaudhary, Eishaina; Poudel, Mukti Ram; Bhandari, Radhakrishna (Journal of Agriculture and Applied Biology, 2023)
Wheat is the third most important cereal crop in Nepal. The impact of global warming is threatening global wheat production and food security. The terminal heat stress reduces the grain quality of wheat. However, the drought is affecting more than 15% of global wheat productivity. To find out the stable and high- yielding wheat genotype the experiment was carried out in Rupandehi, Nepal with twenty genotypes under three different environmental conditions namely heat drought, heat stress and irrigated in an alpha lattice design with two replications in each environment. The AMMI (Additive mean effect multiplicative interaction) biplot analysis shows differences in 20 different genotypes in terms of yield and stability. The analysis of variance model showed the share of GE (genotype and environment) interaction in the variation in grain yield of twenty wheat genotypes. The grain yield of genotype varied significantly with environmental impact (p ). The AMMI stability value (ASV) examined NL1387 as the most stable line. The tested environments were discriminative for genotype and showed negative correlation between them. The GGE biplot analysis was conducted to find out the best performing line under different environments and the stable line in diverse environments. The NL1420 was found stable genotype in all three tested environment. The NL1376 line is most ideal ranking first in the ranking biplot. The mean versus stability model indicated NL1369 and NL1376 as elite genotypes and NL 1404, BL4919 and NL1387 can be recommended as new cultivars.